2022
DOI: 10.3390/molecules27165144
|View full text |Cite
|
Sign up to set email alerts
|

Valorization of the Photo-Protective Potential of the Phytochemically Standardized Olive (Olea europaea L.) Leaf Extract in UVA-Irradiated Human Skin Fibroblasts

Abstract: Leaves of Olea europaea are a by-product of the olive oil industry and a dietary supplement with acknowledged antioxidant and anti-inflammatory activity but underestimated photoprotective potential. We investigated the protective effects of the LC-PDA-MS/MS standardized ethanol-water extract of olive leaves (OLE), containing 26.2% total phenols and 22.2% oleuropein, with underlying mechanisms against the UVA-induced oxidative damage in human dermal fibroblasts. Hs68 cells were pre-treated (24 h) with OLE (2.5–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 47 publications
2
3
0
Order By: Relevance
“…That is supported by previous results from our group, showing that OELE protects dermal fibroblasts in vitro against oxidative stress induced by hydrogen peroxide [28]. Also, other studies have shown the ability of OELE to act as a photoprotective, anti-inflammatory, and antioxidant agent in dermal fibroblasts when exposed to ultraviolet irradiation [53]. In addition, some studies indicate that oleuropein, which, as discussed above, is the most abundant polyphenol in OELE, has positive effects on fibroblasts.…”
Section: Discussionsupporting
confidence: 82%
“…That is supported by previous results from our group, showing that OELE protects dermal fibroblasts in vitro against oxidative stress induced by hydrogen peroxide [28]. Also, other studies have shown the ability of OELE to act as a photoprotective, anti-inflammatory, and antioxidant agent in dermal fibroblasts when exposed to ultraviolet irradiation [53]. In addition, some studies indicate that oleuropein, which, as discussed above, is the most abundant polyphenol in OELE, has positive effects on fibroblasts.…”
Section: Discussionsupporting
confidence: 82%
“…Previous studies have demonstrated the protective role that OLE exerts against oxidative stress in UV-irradiated cells [21,36,37], and these are now further supported by our results that demonstrate the antioxidant activity of the developed materials using the DPPH assay (see Figure 5b).…”
Section: Assessment Of Anti-oxidant Effects In Nhdfssupporting
confidence: 87%
“…Acetoxypinoresinol glucoside was the most abundant lignan in most cultivars, with contents ranging from 494 to 1588 mg kg −1 DW in stems, and 262 to 1001 mg kg −1 DW in roots. The absence of this family of compounds in olive leaves has been widely documented in other works dealing with the LC-MS phenolic profiling of leaves [41,54,55], while other authors have reported very low levels of lignans in this olive tissue [30,39,56].…”
Section: Metabolites Distribution Throughout Plant Tissuesmentioning
confidence: 55%